The Federal Government and Tripartism - Adams, Roy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
Some of the most highly developed tripartite Systems have been established in the Scandinavian countries, in Holland and in Belgium. The difficulties in implementing such a System in Canada are examined.